Atrial fibrillation before heart transplantation is a risk factor for post-transplant atrial fibrillation and mortality - Darche, Fabrice Fernand; Helmschrott, Matthias; Rahm, Ann-Kathrin; Thomas, Dierk; Schweizer, Patrick Alexander; Bruckner, Thomas; Ehlermann, Philipp; Kreußer, Michael; Warnecke, Gregor; Frey, Norbert; Rivinius, Rasmus (ESC heart failure, 2021)
Aims Atrial fibrillation (AF) after heart transplantation (HTX) is associated with worse clinical outcomes. The current study aimed to analyse the association between AF before HTX and AF within 30 days after HTX. Methods and results This study included 639 adults who received HTX at Heidelberg Heart Center. Patients were subdivided into four groups depending on the status of AF before and after HTX. Analyses comprised recipient and donor data, medication, echocardiographic features, permanent pacemaker implantation, stroke, and mortality after HTX. Three hundred thirty-two patients (52.0%) had neither AF before nor after HTX, 15 patients (2.3%) had no AF before HTX but showed AF after HTX, 219 patients (34.3%) showed AF before HTX but had no AF after HTX, and 73 patients (11.4%) had AF before and after HTX. Patients with AF before and after HTX had a higher 1 year post-transplant mortality (39.7%) than patients without AF before or after HTX (18.1%, P < 0.01). Secondary outcomes showed a higher percentage of enlarged atria, ventricular dysfunction, mitral regurgitation, 1-year stroke, and 1-year permanent pacemaker implantation in patients with AF before and after HTX. Multivariate analysis revealed a six-fold elevated risk for post-transplant AF in patients with AF before HTX (hazard ratio: 6.59, confidence interval: 3.72-11.65; P < 0.01). Further risk factors for post-transplant AF were higher donor age and prolonged ischaemic time, whereas total orthotopic HTX was associated with a two-fold lower risk for post-transplant AF. Conclusions Atrial fibrillation before HTX is a risk factor for post-transplant AF, permanent pacemaker implantation, and mortality after HTX.